(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The convergence of wearable and implantable technologies with biomechanics is ushering in a transformative era in precision surgery. This paper presents an integrated framework for NeuroSynced Biointerfaces a novel class of smart wearable and implantable systems designed to capture, analyze, and transmit biomechanical data in real-time to assist surgical procedures. Leveraging advancements in soft biocompatible materials, multimodal sensors, edge-AI processors, and secure wireless communication, these devices act as adaptive interfaces between human physiology and surgical systems. The proposed solution enables high-fidelity physiological monitoring across pre-, intra-, and post-operative phases while supporting real-time feedback loops for robotic-assisted surgeries. Experimental validations using simulation models and prototype deployments demonstrate the feasibility of accurate motion tracking, tissue-state recognition, and physiological telemetry, all while maintaining patient comfort and clinical compatibility. Additionally, the framework incorporates sustainable energy harvesting mechanisms and blockchain-based data management to ensure long-term operational efficiency and data security. This research lays the foundation for next-generation cyber-physical surgical ecosystems, where biosensing intelligence and surgical precision converge to revolutionize personalized and minimally invasive care.